STUDENTS’ EXPERIENCES, CHALLENGES, AND PERCEPTIONS ON U-DICTIONARY TO IMPROVE ENGLISH PRONUNCIATION - Yonri Sudirahayu; Nia Kurniawati; Lidwina Sri Ardiasih (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2024)
This study explores the experiences, challenges, and perceptions of Indonesian senior high school students, specifically those with Sundanese mother tongue backgrounds, as they utilize the